Five recent paradoxes and anomalies of economics - Panchamukhi, V.R. (2000)
This paper presents five major paradoxes and anomalies that characterise recent economic phenomena in the world, viz. (i) the paradox of growth and stability, (ii) the immiserizing effects of structural adjustment, (iii) the paradox of growing unemployment in a framework of full employment goals, (iv) the growth of market imperfections while pursuing a strategy of creating perfectly competitive markets, and (v) the paradox of the World Trade Organization trading system. The paper argues that despite the fact that anomalies and paradoxes have in the past been fertile ground for research the five paradoxes discussed here have not so far received the attention of analysts and of policy makers that they deserve. - Reproduced
Keywords: Economic growth